T.S. Eliot and the Portuguese rule. Navigating between propaganda and cultural diplomacy in the early Salazar dictatorship - Chumbo, Isabel (2024)
T. S. Eliot’s relation with authoritarian regimes has been widely discussed, however his relationship with the propagandistic efforts of the early Salazar dictatorship have not been focused upon. Recent studies within the framework of a doctoral thesis have allowed us to perceive the role of this publisher and editor within the agenda of the Portuguese regime in the 1930s. The unveiling of his correspondence written to Emily Hale by the University of Princeton has also allowed to understand Eliot’s thoughts on his participation in the literary jury of the Camões Award, an event which was part of the cultural diplomacy plan of the Portuguese regime. He was also a pivotal intervenient in the publication of the speeches by Salazar in English, under the aegis of Faber & Faber. This paper has two major objectives: to provide an insight into the role of T. S. Eliot in the Portuguese cultural agenda in the foundational years of the Salazar dictatorship and to analyse his intervention in the translation of the dictator’s speeches into English. This will be made through the analysis of archival and documentational proof available from the Portuguese National Archive and the T. S. Eliot Foundation. As such, this work offers a contribution to the understanding of the Portuguese dictatorship, as well as to the multifaceted character of T. S. Eliot, whose role was relevant not only for the Portuguese cultural diplomacy agenda, but also to the propagandistic efforts carried out by the regime.